1972
DOI: 10.1530/jrf.0.0280055
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adenohypophysial Cells and Levels of Somatotrophin and Prolactin at Different Reproductive Stages in the Pig

Abstract: Percentages of cell types in the adenohypophysis were compared with the content of sth and prolactin at different reproductive stages (e.g. immature, oestrous cycle, pregnancy, lactation and after hysterectomy) in the pig. Acidophils represent sth and prolactin activities. Chromophobes are undifferentiated, inactive or depleted cells.Acidophils represented half (53\m=.\5%) the cell population. Percentages of sth cells were higher in 17-day-old pigs than in mature animals. This is a period of rapid growth in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…From our findings in light microscopy observations, however, the number of GH cells per unit µm2 and the range of immunopositive GH cells across day 1, day 42, and day 100 old animal groups have no significant differences (P > 0.001), which implicate increasing GH level in the young pig is caused by increase not in size but in total number of GH cells as weight or size of the pituitary gland are increased (Table 1). Anderson et al (1972) also pointed out marked increase in GH during later reproductive stages was caused primarily by increase weight of the pituitary gland.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…From our findings in light microscopy observations, however, the number of GH cells per unit µm2 and the range of immunopositive GH cells across day 1, day 42, and day 100 old animal groups have no significant differences (P > 0.001), which implicate increasing GH level in the young pig is caused by increase not in size but in total number of GH cells as weight or size of the pituitary gland are increased (Table 1). Anderson et al (1972) also pointed out marked increase in GH during later reproductive stages was caused primarily by increase weight of the pituitary gland.…”
Section: Discussionmentioning
confidence: 86%
“…There are changes in level of GH and anterior pituitary cells at different reproductive stage in pig. The earlier study (Anderson et al, 1972) showed that the proportion of GH cells was higher in 17-day-old pigs than in any reproductive stages in mature animals because of the rapid growth in the young pig. The finding in the young pig of the highest percentage of GH cells correlated with the extraordinarily high basal plasma growth hormone level (50 to 200 ng/ml) in newborn and 21-day-old pigs (Kipnis et al, 1969).…”
Section: Exocytotic Membrane Fusion Pore In Live Cellsmentioning
confidence: 92%